Reproducibility of the instant of equality of pulmonary gas exchange and its physiological significance - Laplaud, D.; Menier, R. (The Journal of Sports Medicine and Physical Fitness, 2003)
Aim: The goal of this work was to highlight the effectiveness of a new submaximal exercise index of aerobic endurance using a single incremental test: the time at which oxygen uptake and carbon dioxide output are equal, i.e., when the respiratory exchange ratio (RER)=1.00. We studied 2 experimental sets, the 1st to assess the reproducibility and the variability of measured variables, the 2nd to assess the physiological significance of the instant RER=1.00. Methods: The 1st group consisted of 8 subjects who performed 3 maximal ramp tests, the 2nd of 32 athletes. All subjects performed an incremental ramp test until exhaustion with determination of 1st and 2nd ventilatory and lactic thresholds (VT1-LT1, VT2-LT2) and the RER=1.00 instant. Results: There was no significant difference in the used fractions of reserves (UF r) for heart rate, oxygen uptake and power output for RER=1.00 between tests, the coefficients of variation being non-significant. In group 2, there were no significant difference of UF r between VT1 and LT1, VT2 and RER=1.00, LT2 and RER=1.00. In contrast, VT2 differed significantly from LT2. Conclusion: Measurement of the instant of equality of pulmonary gas exchange was therefore reproducible with a low intraindividual variability. Moreover, it exists a concordance of the apparitions of VT1 and LT1 and between these of RER=1.00 and VT2 and LT2. Thus, with the instant RER=1.00 provides the physiologist and the sports physician with an efficient submaximal tool to evaluate aerobic endurance of athletes using a single incremental exercise test.